2020
DOI: 10.1007/s10708-020-10263-8
|View full text |Cite
|
Sign up to set email alerts
|

Everyday geographies in the changing city: subjective photo-routes in Mandalay, Myanmar

Abstract: This work upholds the importance of questioning young people to find out their point of view on urban transformation and grasp their perception and representation of the changes. Hence, the paper presents the methodology and results of an autophotography activity, and more specifically photo-routing organized in March 2018 with a group of young undergraduates at Mandalay University, Myanmar. In the sphere of this activity, the participants were asked to reflect on their relationship with the urban space and to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…In contrast, a study of Instagram content showed there are portraits of one or more people [31], however, the analysis did not distinguish between portraits taken indoors and outdoors. When considering CH, both tangible and intangible instances such as crafts, rites, and ceremonies can be photographic motives [32]. Tourists often visit and photograph heritage sites listed by UNESCO, especially those that are large and have been inscribed early [33].…”
Section: Literature Review 21 Smartphone Photography While Travelingmentioning
confidence: 99%
“…In contrast, a study of Instagram content showed there are portraits of one or more people [31], however, the analysis did not distinguish between portraits taken indoors and outdoors. When considering CH, both tangible and intangible instances such as crafts, rites, and ceremonies can be photographic motives [32]. Tourists often visit and photograph heritage sites listed by UNESCO, especially those that are large and have been inscribed early [33].…”
Section: Literature Review 21 Smartphone Photography While Travelingmentioning
confidence: 99%
“…Although the Harmonized DMSP-OLS dataset attempts to seamlessly integrate the two types of imagery, the DMSP-OLS simulated composites generated for 2013-2018 are unreliable for rural and dimly lit (Digital Number (DN) < 30) areas [76]. Myanmar is sparsely illuminated and has a relatively low (~30%) level of urbanization [79]; therefore, we expected that the DMSP-OLS simulated composites generated from VIIRS data would hold less value for examining the country's dynamics. Inspecting the data confirmed this hypothesis, since the simulated composites showed unusually high gains in NTL between 2012 and 2013 that appeared to be artefacts of the intercalibration process rather than any sudden growth in actual lights ( Figure S1).…”
Section: Data Collection 211 Nighttime Light and Geospatial Datamentioning
confidence: 99%